2008
DOI: 10.1177/0196859908321003
|View full text |Cite
|
Sign up to set email alerts
|

Queer Blogging in Indian Digital Diasporas

Abstract: Queering and transgendering practices have been visible across the Internet since the time of multiuser domains (MUDs), MUD object oriented domains (MOOs), e-mail lists, and Web bulletins. This article maps some themes of queering in the Indian digital diaspora through an intergenerational lens, produced in the acts of online and offline coauthoring, weblogging, and reading of instances of such online queering relationally. By way of a dialogic encounter on their own blogs and employing performative writing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…For instance, Williams's (2007, p. 37) analysis of the content of three blogs run by three gay American college‐age males shows that users could articulate a public queer identity by discussing sexual orientation, same‐sex relationships, or referencing queer culture and/or LGBT and queer (LGBTQ) community affiliations. These techniques were also found by Mitra and Gajjala (2008) in their study of Indian queer blogs. Thus, within the blogosphere, there is a tendency among users to authenticate their individual identities as “real.” That is, they “assert their representations of themselves online as ‘real’ and ‘true’ by incorporating markers such as ‘signatures, photographs, proper first and last names for people and places, and the reportage of experience’ as a way to validate more abstract ideas about the world” (Rak, 2005, p. 175).…”
Section: Subverting Hegemonic Conceptions Of Queernesssupporting
confidence: 64%
“…For instance, Williams's (2007, p. 37) analysis of the content of three blogs run by three gay American college‐age males shows that users could articulate a public queer identity by discussing sexual orientation, same‐sex relationships, or referencing queer culture and/or LGBT and queer (LGBTQ) community affiliations. These techniques were also found by Mitra and Gajjala (2008) in their study of Indian queer blogs. Thus, within the blogosphere, there is a tendency among users to authenticate their individual identities as “real.” That is, they “assert their representations of themselves online as ‘real’ and ‘true’ by incorporating markers such as ‘signatures, photographs, proper first and last names for people and places, and the reportage of experience’ as a way to validate more abstract ideas about the world” (Rak, 2005, p. 175).…”
Section: Subverting Hegemonic Conceptions Of Queernesssupporting
confidence: 64%
“…Dalit groups in India have turned to alternative spaces online, not only to challenge dominant discourse through discursive practices but also to build solidarities nationally and transnationally (Kumar, 2015;Kumar & Subramani, 2014;Mishra, 2017;Nayar, 2011). New media have also had significant impact on queer communities in India, providing them avenues to not only establish their own political narratives but carve a social space for interaction and dialogue (Dasgupta, 2014(Dasgupta, , 2017Mitra & Gajjala, 2008). Within the feminist movement, most recently, following the #MeToo movement in India, hundreds of women came out online with their own narratives of sexual harassment and abuse (Chadha, 2018;Datta, 2017;Gajjala, 2018;Pujari, 2017;Sen, 2017).…”
Section: Nirbhaya: Online Narrative and Digital Activism In Indiamentioning
confidence: 99%
“…Queer diasporic studies have revealed, for instance, that “home” pressures operate with the assimilative demands of “host” societies, deepening the margins for those also subject to misogyny, racism, Islamophobia, and/or eroticisation (ascription of “attractive” ethnic and/or class stereotypes) in lesbian and gay consumer space (Haritaworn, ). Otalvaro‐Hormillosa () suggests these pressures are why “home” is unattainable for many queers, hence the internet's relevance for belonging (Bryant, ; Mitra & Gajjala, ). Even under conditions of person‐to‐person connectivity, spatial media trouble ideas of “freedom” from place whilst strengthening claims against sole emphasis on network flows.…”
Section: Changing Approaches: Network To Assemblagementioning
confidence: 99%
“…Otalvaro-Hormillosa (1999) suggests these pressures are why "home" is unattainable for many queers, hence the internet's relevance for belonging (Bryant, 2015;Mitra & Gajjala, 2008). Even under conditions of person-to-person connectivity, spatial media trouble ideas of "freedom" from place whilst strengthening claims against sole emphasis on network flows.…”
Section: Changing Approaches: Network To Assemblagementioning
confidence: 99%